Diagnosis of inflammatory bowel disease: an international multicentre scoring system. Issue 6309 (9th January 1982) - Clamp, S E; Myren, J; Bouchier, I A; Watkinson, G; de Dombal, F T
Abstract : Inflammatory bowel disease is being studied by the World Organisation of Gastroenterology (OMGE) Research Committee in a survey (currently) affecting 1696 patients presenting to 30 hospitals in 16 countries. A computer-aided diagnostic prediction system (when tested in 1056 patients) showed an accuracy of match between computer prediction and clinical diagnosis in 94% of these patients. Most centres, however, do not possess appropriate computing facilities. A simple diagnostic "scoring system", based on likelihood ratios, has therefore been developed, using a series of numbers set out on a single sheet of paper. The overall accuracy of the simple scoring system in the same 1056 patients was equivalent (93%) to the computer-aided system. In a further series of 510 "new" patients from eight fresh centres the diagnostic scoring system made a firm prediction in 490 cases (96%). Where made, the accuracy of match between the scoring system prediction and clinical diagnosis was 96%. It is suggested that this simple system, which requires no analytical resource and could be used by any gastroenterologist, might be of some value in clinical research and clinical practice.